Motivational goal orientations and the smoking cessation process - Perrine, Nicholas E., author; Aloise-Young, Patricia, advisor; Borrayo, Evelinn A., committee member; Loomis, Ross J., committee member; Lyness, Kevin, committee member (Colorado State University. Libraries, 2005)
Researchers have suggested for years that a "one size fits all" approach to smoking cessation programs may limit their effectiveness. It has further been suggested that the ability to effectively match smokers to treatment programs would represent a major advancement to the field (Shiffman, 1993; Smith & Fiore, 1999). In the present study, individual differences in motivational goal orientations were hypothesized to influence smoking cessation rates due to differences in responses to negative feedback (i.e., inability to quit and relapses) as well as interactions with reward structures of the environment. Participants were 114 adults enrolled in smoking cessation programs. Results suggested that a stronger performance goal orientation was associated with significantly lower quit rates at the 6-month follow-up among research participants who were unable to quit at the 1-month follow-up. Moreover, self-efficacy mediated the relationship between performance goal orientation and quitting. While a significant change in extrinsic rewards was observed, the interaction between motivational goal orientations and intrinsic or extrinsic rewards was not observed to affect smoking cessation rates. Implications for goal orientation theory as well as implications for the design of smoking cessation programs are discussed.
Keywords: social psychology; behavioral sciences; public health; motivation; goal setting; smoking cessation; behavioral psychology